2018
DOI: 10.1175/jcli-d-18-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Precipitation Estimates over the Arctic Ocean and Its Peripheral Seas from Reanalyses

Abstract: Precipitation over the Arctic Ocean has a significant impact on the basin-scale freshwater and energy budgets but is one of the most poorly constrained variables in atmospheric reanalyses. Precipitation controls the snow cover on sea ice, which impedes the exchange of energy between the ocean and atmosphere, inhibiting sea ice growth. Thus, accurate precipitation amounts are needed to inform sea ice modeling, especially for the production of thickness estimates from satellite altimetry freeboard data. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(155 citation statements)
references
References 74 publications
(67 reference statements)
11
143
1
Order By: Relevance
“…These events, in turn, account for between 34% and 55% of the total annual precipitation. Some studies using reanalysis data (e.g., Boisvert et al, 2018) have ignored this light precipitation. Such an approach may be justified on a global scale in light of the tendency for climate models to produce overly frequent drizzle events (e.g., Dai, 2006;Pendergrass & Hartmann, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These events, in turn, account for between 34% and 55% of the total annual precipitation. Some studies using reanalysis data (e.g., Boisvert et al, 2018) have ignored this light precipitation. Such an approach may be justified on a global scale in light of the tendency for climate models to produce overly frequent drizzle events (e.g., Dai, 2006;Pendergrass & Hartmann, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These reanalyses have shown relatively good agreement for air temperature and timing of precipitation events (Merkouriadi, Cheng, et al, ), although there is a warm bias in both products during the lowest temperatures in winter (Graham et al, ). But especially, they exhibit significant differences in the magnitude of precipitation (Boisvert et al, ; Chaudhuri et al, ; Merkouriadi, Cheng, et al, ) with ERA‐I producing relatively low and MERRA‐2 producing relatively high precipitation amounts (Boisvert et al, ; Merkouriadi, Cheng, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kwok et al () showed that the mean levels of ERA‐Interim accumulated snow depths agree well with Operation IceBridge data (Kurtz & Farrell, ) in the limited regions where observations are available. Recently, Boisvert et al () found that the ERA‐Interim reanalysis produces realistic magnitudes and temporal agreement with observed precipitation events . To complement these existing studies, we here additionally compare the ERA‐Interim/MPIOM snow depths to the modified Warren climatology (Laxon et al, ) where that climatology is based on actual measurements.…”
Section: Evaluation Of the Era‐interim‐forced Sea‐ice Statementioning
confidence: 99%